Chemotactic signal transduction and phosphate metabolism as adaptive strategies during citrus canker induction by Xanthomonas citri - Moreira, Leandro Marcio; Facincani, Agda Paula [UNESP]; Ferreira, Cristiano Barbalho [UNESP]; Ferreira, Rafael Marine [UNESP]; Tiraboshi Ferro, Maria Ines [UNESP]; Gozzo, Fabio Cesar; Franco de Oliveira, Julio Cezar; Ferro, Jesus Aparecido [UNESP]; Soares, Marcia Regina (Springer, 2015)
The genome of Xanthomonas citri subsp. Citri strain 306 pathotype A (Xac) was completely sequenced more than 10 years; to date, few studies involving functional genomics Xac and its host compatible have been developed, specially related to adaptive events that allow the survival of Xac within the plant. Proteomic analysis of Xac showed that the processes of chemotactic signal transduction and phosphate metabolism are key adaptive strategies during the interaction of a pathogenic bacterium with its plant host. The results also indicate the importance of a group of proteins that may not be directly related to the classical virulence factors, but that are likely fundamental to the success of the initial stages of the infection, such as methyl-accepting chemotaxis protein (Mcp) and phosphate specific transport (Pst). Furthermore, the analysis of the mutant of the gene pstB which codifies to an ABC phosphate transporter subunit revealed a complete absence of citrus canker symptoms when inoculated in compatible hosts. We also conducted an in silico analysis which established the possible network of genes regulated by two-component systems PhoPQ and PhoBR (related to phosphate metabolism), and possible transcriptional factor binding site (TFBS) motifs of regulatory proteins PhoB and PhoP, detaching high degree of conservation of PhoB TFBS in 84 genes of Xac genome. This is the first time that chemotaxis signal transduction and phosphate metabolism were therefore indicated to be fundamental to the process of colonization of plant tissue during the induction of disease associated with Xanthomonas genus bacteria.
Keywords: Xanthomonas adaptation; Chemotaxis signal transduction; Phosphate metabolism; Two-component systems PhoBR and PhoPQ; Virulence